Effect of training with vascular occlusion on muscle power in the bench press exercise in trained adults - Arenas Sánchez, Giovanny.; Mamani Tapia, Braulio.; Inostroza Téllez, Eduardo Francisco.; Peiret Villacura, Luis.; Farías Valenzuela, Claudio Ítalo.; Orellana Montini, Javier.; Espinoza Salinas, Alexis. (Universidad de Murcia, 2023)
Introduction: Blood Flow Restriction Training (BFRT), combines exercise and partial blood flow reduction with positive effects on the development of muscle hypertrophy. However, there is still a marked inconsistency in the effects it generates on the development of muscle power. Objective: This study aims to analyze the effect of upper extremity vascular occlusion training on muscle power in trained adults. Methods: Quasi-experimental study with control group in 12 subjects, mean age 28 (± 1.3) years. Purposive, non-probabilistic sampling. Divided into two groups; i) intervened group, which performed an BFRT protocol at 30% of 1 repetition maximum (1RM); ii) traditional training group, performed training at 70% of 1RM. Each group performed 12 bench press training sessions. Results: BFRT increased mean power (p = 0.01); concentric power (p = 0.04) and eccentric power (p = 0.01). Discussion: El EOV mostró mejoras en potencia muscular, lo que se condice por lo reportado en la literatura en otras poblaciones. Se debe considerar que la presión de oclusión debe ser adaptada para cada participante para evitar riesgos en la salud. Conclusion: 12 sessions of low-load muscular strength training with vascular occlusion improve the muscular power of the upper extremities in the bench press exercise in a sample of trained adults.
Efecto del entrenamiento con oclusión vascular sobre la potencia muscular en el ejercicio de press banca en adultos entrenados
Keywords: Entrenamiento con oclusión vascular; Entrenamiento de fuerza; Potencia muscular; Hipoxia muscular; Hipertrofia muscular; Estrés metabólico; Restricción de flujo sanguíneo; Entrenamiento KAATSU